Upper Semicontinuity of Attractors for a Non-Newtonian Fluid under Small Random Perturbations - Jianxin Luo (Abstract and Applied Analysis)
This paper investigates the limiting behavior of attractors for a two-dimensional incompressible non-Newtonian fluid under small random perturbations. Under certain conditions, the upper semicontinuity of the attractors for diminishing perturbations is shown.